2021
DOI: 10.1038/s41598-021-96346-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-generation and sound intensity interactively modulate perceptual bias, but not perceptual sensitivity

Abstract: The ability to distinguish self-generated stimuli from those caused by external sources is critical for all behaving organisms. Although many studies point to a sensory attenuation of self-generated stimuli, recent evidence suggests that motor actions can result in either attenuated or enhanced perceptual processing depending on the environmental context (i.e., stimulus intensity). The present study employed 2-AFC sound detection and loudness discrimination tasks to test whether sound source (self- or external… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 94 publications
(212 reference statements)
1
16
0
Order By: Relevance
“…Consequently, perceptual bene ts of actively generated stimuli might be overestimated, if the stimulus order is not counterbalanced (Myers et al, 2020). However, preceding studies using a similar experimental setup show results compatible with our ndings (Reznik et al, 2015;Paraskevoudi & SanMiguel, 2021). Further, combining active and passive trials, the results of our study did not imply a general response bias towards the rst tone (Figure S3).…”
Section: Stimulus Order Effectssupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, perceptual bene ts of actively generated stimuli might be overestimated, if the stimulus order is not counterbalanced (Myers et al, 2020). However, preceding studies using a similar experimental setup show results compatible with our ndings (Reznik et al, 2015;Paraskevoudi & SanMiguel, 2021). Further, combining active and passive trials, the results of our study did not imply a general response bias towards the rst tone (Figure S3).…”
Section: Stimulus Order Effectssupporting
confidence: 86%
“…Note that our results show relatively small differences between proportions of responses in which participants judged the loudness of the test stimuli as higher than the loudness of the standard. Comparing the results of our online experiment with other studies including a similar experimental set-up, but that were conducted in a laboratory environment (Reznik et al, 2015;Paraskevoudi & SanMiguel, 2021), we found relatively small deviations from perceived equality of loudness judgements (mean ± standard error of the mean: active: 53.0 ± 1.2%, passive: 48.9 ± 1%; Reznik et al (2015): active: 61.4 ± 2.1%, passive: 56.2 ± 2.1%; Paraskevoudi & SanMiguel (2021): active: 46.1 ± 3.9%, passive: 53.6 ± 3.7%). This might be due to the lack of control over the noise of the participant's environment, and the di culty to determine the exact stimulus intensity due to individual differences in technical set-ups.…”
Section: Discussionmentioning
confidence: 95%
“…However, while predictive cancellation has seemed foundational to successful theories of action control and awareness, research in recent years has begun to undermine the idea that predicted action outcomes really are cancelled. An emerging body of work has begun to show thatcontrary to classic ideasexpected action outcomes may be perceptually and neurally enhanced Dogge, Custers, Gayet, et al, 2019;Guo & Song, 2019;Paraskevoudi & SanMiguel, 2021;Reznik et al, 2014Reznik et al, , 2021Reznik & Mukamel, 2019;Thomas et al, 2022;Yon et al, 2018Yon et al, , 2021Yon et al, , 2022; see also Hudson et al, 2015Hudson et al, , 2018. These findings accord with a general picture of perceptual prediction described by Bayesian models which stress that it is adaptive for agents to bias their perceptual inferences towards what they expect, perhaps via increasing the gain on expected sensory channels (Bar, 2004;Yuille & Kersten, 2006;Press et al, 2020a).…”
Section: Introductionmentioning
confidence: 53%
“…It should be noted that previous studies using the same type of discrimination task observed different effects of the active condition on these two parameters Paraskevoudi and SanMiguel, 2021). For example, Paraskevoudi and SanMiguel (2021) found reduced perceived intensity (i.e., perceptual bias) for self-generated sounds when presented at supra-threshold intensities (high level), but which increased when presented at near-threshold intensities (low level).…”
mentioning
confidence: 93%